DEVELOPMENT OF WEB-BLOG-BASED LEARNING MEDIA USING PROBLEM-BASED LEARNING MODEL - Meike Paat; Yohanes Bery Mokalu (SOSCIED, 2023)
The objective of this research is to develop a web blog-based science learning media. The study utilizes the research and development method by Borg and Gall and was conducted at SMP Negeri 7 Manado from March to June in the academic year 2022/2023. The field trial subjects comprised subject matter experts, instructional media experts, students, and teachers. Data collection instruments included questionnaires, interviews, and observations. The obtained data were analyzed significantly. The results of the expert validation for the product materials fall into the valid category with a score of 87.39%. The expert validation for the instructional media product is also categorized as valid with a score of 88.82%. The results of the limited-scale field trial fall into the valid category with 67.90% of students choosing strongly agree and 32.10% choosing agree. The results of the full-scale field trial fall into the valid category with 77.77% of students choosing strongly agree and 22.23% choosing agree. This study concludes that the web blog-based science learning media is effective, efficient, engaging, and suitable for use in classroom.